Oxytocin, GABA, and dopamine interplay in autism - Havranek Tomas; Bacova Zuzana; Bakos Jan (Endocrine Regulations)
Oxytocin plays an important role in brain development and is associated with various neurotransmitter systems in the brain. Abnormalities in the production, secretion, and distribution of oxytocin in the brain, at least during some stages of the development, are critical for the pathogenesis of neuropsychiatric diseases, particularly in the autism spectrum disorder. The etiology of autism includes changes in local sensory and dopaminergic areas of the brain, which are also supplied by the hypothalamic sources of oxytocin. It is very important to understand their mutual relationship. In this review, the relationship of oxytocin with several components of the dopaminergic system, gamma-aminobutyric acid (GABA) inhibitory neurotransmission and their alterations in the autism spectrum disorder is discussed. Special attention has been paid to the results describing a reduced expression of inhibitory GABAergic markers in the brain in the context of dopaminergic areas in various models of autism. It is presumed that the altered GABAergic neurotransmission, due to the absence or dysfunction of oxytocin at certain developmental stages, disinhibits the dopaminergic signaling and contributes to the autism symptoms.